Evaluation of Hypoglycaemic Activity of Some Medicinal Plants of Satpuda Forest on Alloxan Induced Diabetes in Rats - Lohar2, Jaytee M. Sonawane1*; Prakash S. (Journal of Ecobiotechnology, 2011)
Diabetes mellitus is a common endocrine disorder characterized by insufficient or lack of insulin and impaired carbohydrate metabolism in the body leading to long-term complications affecting the eyes, nerves, blood vessels, skin, and kidneys. There is an estimated 143 million people worldwide suffering from diabetes: a figure which is almost five times as much as the estimates ten years ago. In spite of the presence of antidiabetic drugs in pharmaceutical market, there is an increasing demand by patients to use the herbal products having hypoglycaemic activity. There have been reports on the hypoglycaemic activity of Gymnema sylvestre (Gurmar), Eugenia jambolana (Jamun), Momordica charantia (Karela) and Alstonia scholaris (Satwan) on individual plant basis. The present work was undertaken to study the antidiabetic effect of the individual plant extract and the composite of G. sylvestre, E. jambolana, M. charantia and A. scholaris on healthy and alloxan induced diabetic rat models. In the in vivo experiments, oral administration of individual plant extract and their composite in an appropriate concentration in normal and alloxan induced diabetic rats were evaluated. Blood samples from normal and experimental animals were collected and assayed for blood glucose level (BGL) and plasma insulin level (PIL). Results showed that there was significant reduction in blood glucose level and increase in plasma insulin level due to oral administration of extracts derived from G. sylvestre, E. jambolana, M. charantia and A. scholaris in alloxan induced diabetic rat models on individual plant basis but not in normal rats (p<0.05).Ã‚Â As compared to administration of individual plant extract, the composite of all four plants shown highly significant decrease in BSL and augmentation in PIL in alloxan induce diabetic rats. It is concluded that the combined extracts from four plants proved its potentially excellent hypoglycaemic activity and such polyherbal therapy could be use in the management of diabetes.